TRIBRATA NEWS' COMMUNICATION STRATEGY IN THE DIGITAL ERA - Ahmad Mustofa Kamal; Ahmad Muhaemi; Santi Intan Anansih; Sa'diyah El Adawiyah (Perspektif Komunikasi Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2025)
In the midst of an era of information disruption, the legitimacy of police institutions is no longer simply determined by legal authority, but by its ability to win public trust in the digital space. This research highlights the urgency of transforming the communication strategy of the Public Relations Division of the National Police through the Tribrata News ecosystem which is now integrated with PoliceTube and Smart Public Relations. Based on Dialogic Communication Theory and the concept of Computer-Mediated Communication, this study criticizes the shift in the communication paradigm of the National Police from a bureaucratic-monologue model to a humanist-dialogical model. Using a descriptive qualitative method with a digital case study approach, this study dissects how the integration of news channels, visual storytelling, and instant messaging services works as a communication orchestra to break down the hierarchical barriers between officials and citizens. The findings of the study show that the "One Message, Three Channels" strategy has succeeded in changing the digital face of the National Police to be more serving and responsive. PoliceTube plays a role in deconstructing rigid imagery through an empathetic visual narrative, while Smart Public Relations bridges the need for real-time access transparency. This study concludes that digitalization in the National Police is not just a modernization of tools, but a cultural revolution from a "command" mentality to a "guardianship". Although HR competency challenges are still identified, this integrated communication model has proven effective in building authentic public engagement. This study recommends the need to strengthen digital ethics and empathy in every machine-human interaction to maintain the sustainability of public trust.